Preparation and Evaluation of Diclofenac Sodium Polyelectrolyte Microparticles for Controlled Drug Delivery - Srinivas, L. (Asian Journal of Chemistry, 2011)
The electrostatic interactions between oppositely charged polyelectrolytes lead to formation of insoluble polyelectrolyte complexes in aqueous medium. The polyelectrolyte complexes formed between a poly acid and poly base are little affected by the pH variation of the dissolution medium. In the present study attempts were made to prepare polyelectrolyte complexes of polyvinyl pyrrolidone (poly base) and carbopol (poly acid) into which diclofenac sodium is incorporated and studied for its controlled release. The polyelectrolyte complexation was evaluated by pH, conductivity, Fourier transform infrared spectroscopy, X-ray diffractometry and scanning electron microscopy studies. The dried polyelectrolyte complexes were also evaluated for micromeritic properties and drug release kinetics. Promising results were obtained suggesting the application of these polyelectrolyte microparticles of diclofenac sodium in the design of controlled release systems.